Der Spröd-duktil-Übergang in ultrafeinkörnigem Wolfram - Bonnekoh, Carsten (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2023)
High brittle-ductile transition temperatures preclude the use of conventionally manufactured tungsten (W) as a structural material. Ultrafine grained (UFG) W materials, however, exhibit the brittle-ductile transition at very low temperatures and consequently exhibit room-temperature ductility. The correlative microstructure analysis revealed a strong correlation between the transition temperature and the mean grain boundary spacing along the crack front.